The terminal sequences of Bombyx mori 18S ribosomal RNA. - Sprague, K U (1975)
The 5' and 3' terminal T1 oligonucleotides of 32p-labelled B. mori 18S ribosomal RNA were isolated by a two dimensional electrophoretic (diagonal) technique. Nucleotide sequence analysis showed that the 3' terminal fragment, (G)AUCAUUAOH, is identical to that previously obtained from the 18S rRNA of several other eukaryotic species. The sequence of the B. mori 5' terminal fragment is pUCCUCG.